Crises (Staseis) and Changes (Metabolai) Athenian Democracy in the Making - Battistin Sebastiani, Breno; Ferreira Leão, Delfim (Studi e saggi, 2022)
This book aims to build a solid and proper contribution to the contemporary global debate on the experience of democracy and its possibilities as the most effective mediator of a series of challenges, a debate that is necessarily rooted in the critical reassessment of its Greek cultural heritage. The book is articulated around the identification of a concrete problem: the need for studies that critically discuss Athenian democracy, seen as a daily problem and practice, based on its staseis (crises) and metabolai (changes), and whose solutions and strategies may still contribute to the reflection on the social, intellectual and ethical-political challenges of contemporary democracy.